The Influence of Micro Teaching Implementation for The Field Practicing Students of IAKN Tarutung - Rusmauli Simbolon (ADI Publisher, 2020)
The purpose of this study was to clarify how much the influence of the implementation of micro teaching for the field practicing students. The research method was descriptive and inferential quantitative research. The population in this study was all 2018 academic students with a total of 210 students with a sample of 63 amount. Data were collected by 33 questionnaire items. The results of the data analysis showed that there was a positive and significant effect of the implementation of micro teaching upon the field practicing students.The research result showed that t-obt = 7,087 t(tabel(=0,05,df=n-2=61) = 0.05, df = n-2 = 61) = 2, Hypothesis testing using the F test of which Fobt > Ftabel is 50.22 > 1.39 thus H0 was rejected and Ha was accepted which means that micro teaching has positive and significant effect upon the Field Practicing students of IAKN Tarutung in academic year of 2017- 2018.